Elderberry and Elderflower (Sambucus spp.): A Cultivation Guide for Florida - David Jarnagin; Ali Sarkhosh; Juanita Popenoe; Steve Sargent; Kevin Athearn (EDIS, 2020)
The purpose of this new 9-page paper, written by David Jarnagin, Ali Sarkhosh, Juanita Popenoe, Steve Sargent, and Kevin Athearn, and published by the UF/IFAS Horticultural Sciences Department, is to provide information on growing American elderberry in Florida as an alternative crop for commercial growers as well as homeowners. Although elderberry has been historically grown at commercial scale in some world regions, especially throughout Europe, in the New World it has not found meaningful commercial acceptance until recently. https://edis.ifas.ufl.edu/hs1390